Bactérias como agentes de controle de Phytophthora nicotianae e como promotoras de crescimento de porta-enxertos de citros - Giassi, Valdionei (2015)
The microbial community plays an essential role in maintaining the ecological balance of soil. Interactions between microorganisms and plants have a major influence on the nutrition and health of the latter, and growth-promoting rhizobacteria can be used to improve plant development through a wide range of mechanisms. Therefore, the objective of the present study was to evaluate bacteria as biological control agents to Phytophthora nicotianae and as growthpromoting agents for citrus rootstocks. Altogether were evaluated 30 bacterial isolates, 11 Bacillus spp., 11 actinobacteria, and 8 lactic acid bacteria. For P. nicotianae control tests at first was performed an bioassay with alfalfa seedling in order to select the most promising bacterial isolates for the biocontrol and, posteriorly, the best isolates were applied in Sunki mandarin (Citrus sunki Hort. ex Tan), and rangpur (Citrus × limonia Osbeck) by seeds and substrate microbiolization methods. It was evaluated the number of surviving plants, at 90 days after sowing and inoculation. The same Isolates also were evaluated in vitro for indoleacetic acid production, phosphate solubilization, and nitrogen (N) fixation. In vivo testing consisted of growth promotion trials of the bacterial isolates that yielded the best results on in vitro tests with three rootstocks: Swingle citrumelo [Citrus × paradisi Macfad cv. Duncan × Poncirus trifoliata (L.) Raf.], Sunki mandarin and rangpur. The parameters of interest were height, number of leaves, stem diameter, shoot and root dry mass, and total dry mass at 150 days after germination. The results showed that alfalfa seedling bioassay vi was able to evaluate the potential for biocontrol of bacterial isolates against to P. nicotianae, BL06 and BL12 (both lactic acid bacteria) showed potential to be used as biocontrol agents of disease, independently from the application method. BM16 and CPMO4 were able to promote growth of Swingle citrumelo. In Sunki mandarin plants, the best treatment results were obtained with BM17 (Bacillus sp.) and ACT11 (actinobacteria). For Rangpur lime rootstock, only BM05 (Bacillus sp.) was able to promote increase in two parameters assessed, height and number of leaves.